Clothing comfort during physical exercise – Determining the critical factors. (November 2018) - Raccuglia, Margherita; Sales, Benjamin; Heyde, Christian; Havenith, George; Hodder, Simon
Abstract: Clothing comfort is determined by multiple material and design factors. Wetness at the skin-clothing interface mainly impacts wear comfort. The current study investigated the combined effect of fabric contact area, fabric absolute sweat content and fabric moisture saturation percentage on wetness and stickiness sensations, during exercise. Moreover, factors causing wear (dis)comfort during exercise were identified. Higher fabric saturation percentage induced greater stickiness sensation, despite lower fabric contact area and absolute sweat content (typically associated with lower stickiness). Wetness perception did not change between fabrics with different saturation percentages, contact areas and sweat contents. Therefore, fabric saturation percentage mainly affects stickiness sensation of wet fabrics, overruling the impact of fabric contact area and absolute sweat content. No overall model of wear discomfort across all data could be developed, however, models for different time points were produced, with texture and stickiness sensations being the best predictors of wear discomfort at baseline and during exercise, respectively. This suggests that the factors determining clothing (dis)comfort are dynamics and alter importance during exercise activity.